Research on the stability against overturning for EMU bogie with inner axle box suspension - SU Rui; FU Maohai; LI Ziang; CHE Yunhang (机车电传动)
Due to the built-in axle box suspension, the EMU bogie with an inner axle box causes an obvious decrease in the anti-roll stiffness of the carbody and accordingly affects the running performance. The inner axle box bogie is usually accompanied with the measures of installing anti-rolling torsion bars and increasing the vertical stiffness of primary suspension, in order to improve the stability against overturning of the carbody. This paper proposed an anti-overturning device special for the EMU bogie with an inner axle box. It consisted of two disconnected circuits installed between the wheelset axle box and the frame. After analyzing the basic principle and stiffness characteristics of the anti-overturning device and vehicle dynamics model, co-simulation was performed to generate the dynamics performance and dynamic envelope of the vehicle passing large radius curves at various speeds by MATLAB/Simulink, AMESim and SIMPACK. The results show the effectiveness of the anti-overturning device to increase the anti-roll ability of the vehicle while maintaining the running stability, and the better safety indicators such as derailment coefficient and wheelset lateral force, in addition to a smaller dynamic envelope.